Breast reconstruction with the deep inferior epigastric perforator flap is a reliable alternative in slim patients. Issue 7 (3rd November 2015) - Mani, Maria; Wang, Tim; Harris, Paul; JAMES, Stuart
Abstract : Introduction: For slim patients eligible to breast reconstruction, clinical concerns exist on availability of adequate amount of donor tissue to restore breast volume and challenges in donor‐site closure, when using the deep inferior epigastric perforator (DIEP) flap. The purpose of the current study is to analyze whether the DIEP flap can provide adequate volume for breast reconstruction in slim patients, without increased complication rates or prolonged hospital stay. Patients and methods: All patients receiving a unilateral DIEP breast reconstruction at the center 2007‐2010 were included ( n  = 171). The patients were analyzed in subgroups of delayed and immediate reconstruction and of BMI. Complications were analyzed according to Clavien‐Dindo. Flap weight was compared to mastectomy specimen weight among immediate reconstructions ( n  = 91). Results: There was no difference in specimen to flap weight ratio between the different BMI‐groups (BMI <25, 25‐29.9 and >30: 0.81, 0.87 and 0.96 respectively, P  = 0.360. Overall complication rate was 43.1% (BMI <25); 43.0% (BMI 25‐29.9): and 70.0% (BMI >30) ( P  = 0.018). The results were similar for both the immediate and the delayed reconstructions. Length of hospital stay was similar in the different BMI groups. Delayed donor‐site healing was higher in patients with BMI <25; 17.2%, compared to patients with BMI 25‐29.9; 11.8%, but lower than for patients with BMI >30; 29.7% ( P  = 0.033). Conclusion: The DIEP flap provides adequate volume for unilateral breast reconstruction in slim patients, both in immediate and delayed settings. However, in delayed reconstructions slim patients need to be informed about the increased risk of donor‐site complications. © 2015 Wiley Periodicals, Inc. Microsurgery 36:552–558, 2016.